The unique biogeochemical role of carbonate-associated organic matter in a subtropical seagrass meadow - Mary A. Zeller; Bryce R. Van Dam; Christian Lopes; Amy M. McKenna; Christopher L. Osburn; James W. Fourqurean; John S. Kominoski; Michael Ernst Böttcher (Communications Earth & Environment)
Abstract The particulate organic matter buried in carbonate-rich seagrass ecosystems is an important blue carbon reservoir. While carbonate sediments are affected by alkalinity produced or consumed in seagrass-mediated biogeochemical processes, little is known about the corresponding impact on organic matter. A portion of particulate organic matter is carbonate-associated organic matter. Here, we explore its biogeochemistry in a carbonate seagrass meadow in central Florida Bay, USA. We couple inorganic stable isotope analyses (δ34S, δ18O) with a molecular characterization of dissolved and carbonate associated organic matter (21 tesla Fourier-transform ion cyclotron resonance mass spectrometry). We find that carbonate-associated molecular formulas are highly sulfurized compared to surface water dissolved organic matter, with multiple sulfurization pathways at play. Furthermore, 97% of the formula abundance of surface water dissolved organic matter is shared with carbonate-associated organic matter, indicating connectivity between these two pools. We estimate that 9.2% of the particulate organic matter is carbonate-associated, and readily exchangeable with the broader aquatic system as the sediment dissolves and reprecipitates.